The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/rcm.2925
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbon and nitrogen stable isotopes of chironomid larvae during growth, starvation and metamorphosis

Abstract: We conducted experiments to determine isotope changes in the deposit-feeding chironomid larvae Chironomus acerbiphilus during feeding, starvation and metamorphosis. Isotope changes in chironomid larvae occurred mainly during growth and rarely afterward. This finding indicates that chironomid isotope turnover mainly occurs in conjunction with growth and suggests that chironomid larvae only break down newly assimilated food for energy during periods of no growth. Chironomid delta(13)C values significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 22 publications
6
64
0
Order By: Relevance
“…For wasps, after the egg hatches, they feed mainly on caterpillars (hunted by adult worker wasps) during their larva stage, and do not feed during metamorphose in cocoons during their chrysalis stage (e.g., Takamizawa 2005). In a previous study on the Diptera Chironomus acerbiphilus (Doi et al 2007), metamorphosis resulted in an increase of between 0.7 and 1.6& in d 15 N values of bulk tissues from larva to adult. Similar increases in d 15 N values have been observed for Lepidoptera (McCutchan et al 2003;Tabbets et al 2008) and Neuroptera (Patt et al 2003).…”
Section: Effect Of Metamorphosismentioning
confidence: 88%
“…For wasps, after the egg hatches, they feed mainly on caterpillars (hunted by adult worker wasps) during their larva stage, and do not feed during metamorphose in cocoons during their chrysalis stage (e.g., Takamizawa 2005). In a previous study on the Diptera Chironomus acerbiphilus (Doi et al 2007), metamorphosis resulted in an increase of between 0.7 and 1.6& in d 15 N values of bulk tissues from larva to adult. Similar increases in d 15 N values have been observed for Lepidoptera (McCutchan et al 2003;Tabbets et al 2008) and Neuroptera (Patt et al 2003).…”
Section: Effect Of Metamorphosismentioning
confidence: 88%
“…Consumers with a larger body size are expected to reach tissue equilibrium more slowly than smaller organisms and may assimilate less 15 N label over a shortterm (14 d) experiment such as ours. We based our assumption of tissue equilibrium on the larger size but high level of enrichment in Nereis diversicolor during the experiment (mudflat; see Table 2) and rapid tissue turnover times reported (Doi et al 2007) for both C and N in deposit-feeding chironomids of a mass similar to the annelids studied here. In the Doi et al 2007 study, isotope equilibrium was reached at 12 d. To determine source contributions in the enrichment model, we used the natural abundance δ 13 C values averaged over the 21 d experiment plus δ E .…”
Section: Methodsmentioning
confidence: 99%
“…We based our assumption of tissue equilibrium on the larger size but high level of enrichment in Nereis diversicolor during the experiment (mudflat; see Table 2) and rapid tissue turnover times reported (Doi et al 2007) for both C and N in deposit-feeding chironomids of a mass similar to the annelids studied here. In the Doi et al 2007 study, isotope equilibrium was reached at 12 d. To determine source contributions in the enrichment model, we used the natural abundance δ 13 C values averaged over the 21 d experiment plus δ E . Sources were spatially distinct among habitats, and we therefore varied the primary producers used in mixing models depending on habitat.…”
Section: Methodsmentioning
confidence: 99%
“…Because the trophic enrichment factor is key to determining consumer trophic level (Gannes et al 1997), many laboratory experiments have sought to identify potential factors that can affect trophic enrichment. These studies have shown that developmental stage (Doi et al 2007), quality of diet items (Oelbermann and Scheu 2002), diet isotopic ratios (Caut et al 2008), and type of body tissues used for the analyses (DeNiro and Epstein 1978;Tieszen et al 1983) can influence enrichment factors. Meta-analyses have demonstrated that taxon, the associated biochemical form of excreted N, and feeding habits are also important determinants of trophic enrichment (McCutchan et al 2003;Vanderklift and Ponsard 2003;Caut et al 2009).…”
Section: Introductionmentioning
confidence: 98%